2014
DOI: 10.5539/jas.v6n12p251
|View full text |Cite
|
Sign up to set email alerts
|

Increases of Unsaturated Fatty Acids in Membrane Lipids Protects Photosystem II from Photoinhibition under Salinity in Different Halophytes

Abstract: For the purpose of testing the function of unsaturated fatty acids in different halophytes in the process of photosynthesis under salt stress, the impact of saline stress on plant development, content of chlorophyll, the PSII photochemistry efficiency, content of membrane lipid and composition of fatty acid were investigated in the three halophytes Thellungiella halophila, Limonium bicolor and Suaeda salsa and non-halophyte Arabidopsis thaliana. Salinity (200 mM NaCl) did not reduce the value of Fv/Fm, ΦPSII, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Many experiments suggest that changes in unsaturated fatty acid content can enhance the plant tolerance to environmental stresses such as cold, heat and drought (Dakhma et al, 1995;Matos et al, 2002;Sui et al, 2007a, 2007b, Sui & Han, 2014. Our former study suggested that S. salsa displays high resistance to photoinhibition under salt stress conditions and that increased concentration of unsaturated fatty acids in membrane lipids of S. salsa enhances the tolerance of photosystem II to salt stress (Sui et al, 2010;Sui et al, 2007b).…”
Section: Discussionmentioning
confidence: 92%
“…Many experiments suggest that changes in unsaturated fatty acid content can enhance the plant tolerance to environmental stresses such as cold, heat and drought (Dakhma et al, 1995;Matos et al, 2002;Sui et al, 2007a, 2007b, Sui & Han, 2014. Our former study suggested that S. salsa displays high resistance to photoinhibition under salt stress conditions and that increased concentration of unsaturated fatty acids in membrane lipids of S. salsa enhances the tolerance of photosystem II to salt stress (Sui et al, 2010;Sui et al, 2007b).…”
Section: Discussionmentioning
confidence: 92%
“…This plasticity can be useful for biotechnological purposes, since environment manipulation can be used to increase the nutritional value of macrophytes, as it is performed for other marine species [ 27 ]. For example, it has been described that high salinity increases the content of 16:3 n -3 and 18:3 n -3 in Ulva pertusa [ 19 ] as well as PUFAs in halophytes ( Thellungiella halophile , Limonium bicolor and Suaeda salsa ) [ 28 , 29 , 30 ]. The effect of light was also studied by Floreto et al [ 31 ] in three species of macroalgae ( Ulva pertusa , Grateloupia sparsa and Sargassum piluliferum ), who showed that high light intensity increases the content of SFA.…”
Section: Bioactive Lipids From Marine Macrophytesmentioning
confidence: 99%
“…Apart from being time-consuming, other major disadvantages of this approach are its low resolution and sensitivity. TLC has been widely used to ascertain the polar lipidome of marine macrophytes, generally followed by off-line structural characterization; the majority of this characterization is performed by gas chromatography (GC) [ 21 , 26 , 29 , 45 , 60 , 61 , 63 , 65 ] or MS [ 39 , 52 , 57 , 107 , 108 ].…”
Section: Strategies For Lipid Analysis From Marine Macrophytes: Frmentioning
confidence: 99%
“…The higher content of PE in comparison to PC and the presence of more unsaturated fatty acids (linolec, 18:2 and linolenic, 18:3) was observed in embryogenic membranes of wheat calli (Laggner et al 2003). Earlier, Reidiboym-Talleux and Grenier-De March (1999) in studies of Prunus savium found that embryogenic calli were characterized by a higher content of total phospholipids compared to nonembryogenic ones and that this may be explained by the Evans et al 1990;Palta et al 1993;Aziz and Larher 1998;Quartacci et al 2001;Nouairi et al 2006;Sui and Han 2014 PE 25.2-58.0 1.2-10.6 1.9-13.6 15.0-60.0 4.6-66.5 Browse et al 1986;Aziz and Larher 1998;Evans et al 1990;Palta et al 1993;Quartacci et al 2001;Nouairi et al 2006 PG 21.0-44.6 1.9-12.0 2.6-12.2 6.0-36.4 5.5-72.8 Browse et al 1986;Chapman et al 1986;Quartacci et al 1995Quartacci et al , 2001Aziz and Larher 1998;Sui and Han 2014 PA 20.0-48 Chapman et al 1986;Evans et al 1990;Quartacci et al 1995;Aziz and Larher 1998;Campos et al 2003;Nouairi et al 2006;Filek et al 2009;Sui andHan 2014 DGDG 1.0-47.7 0.7-19.3 0.1-10.4 1.2-28.5 15.7-87.7 Browse et al 1986;Chapman et al 1986;Evans et al 1990;Quartacci et al 1995;Aziz and Larher 1998;Kaniuga et al 1999;…”
Section: Tablementioning
confidence: 99%
“…The composition of the main lipid fractions in plasmalemma chloroplast and microsomal membranes of various plants in ( 3.4-54.3 1.0-28.0 Allen et al 1964;Galliard 1968;Roughan and Batt 1969;Wintermans 1960;Harwood 1975Harwood , 1980Sheppard et al 1978;Evans et al 1990;Palta et al 1993;Quartacci et al 1995Quartacci et al , 2001Uemura et al 1995;Hernandez and Cooke 1997;Gniazdowska et al 1999;Welti et al 2002;Nouairi et al 2006;Salama et al 2007;Toumi et al 2008;Filek et al 2009;Zamani et al 2010;Cacho et al 2012;Ibrahim et al 2012;Li et al 2014;Sui and Han 2014 Chloroplast 6.7-32.0…”
Section: Tablementioning
confidence: 99%